Elsewhere [compact disc, unabridged] - Zevin, Gabrielle (Listening Library, 2005)
After fifteen-year-old Liz Hall is hit by a taxi and killed, she finds herself in a place that is both like and unlike Earth, where she must adjust to her new status and figure out how to "live."